Use of Herbal Medicine by Pregnant Women: What Physicians Need to Know - Illamola, Sílvia M.; Amaeze, Ogochukwu U.; Krepkova, Lubov V.; Birnbaum, Angela K.; Karanam, Ashwin; Job, Kathleen M.; Bortnikova, Valentina V.; Sherwin, Catherine M.T.; Enioutina, Elena Y. (Frontiers in Pharmacology, 2020)
About 80% of consumers worldwide use herbal medicine (HMs) or other natural products. The percentage may vary significantly (7-55%) within pregnant women, depending upon social status, ethnicity and cultural traditions. This manuscript discusses the most common HMs used by pregnant women and the potential interactions of HMs with conventional drugs in some medical conditions that occur during pregnancy (e.g., hypertension, asthma, epilepsy). It also includes an examination of the characteristics of pregnant HM consumers, the primary conditions for which HMs are taken, and a discussion related to the potential toxicity of HMs taken during pregnancy. Many cultures have used HMs in pregnancy to improve the wellbeing of mother and baby or help to decrease nausea and vomiting, treat infection, ease gastrointestinal problems, prepare for labor, induce labor, or ease labor pains. One of the reasons why pregnant women use HMs is an assumption that HMs are safer than conventional medicine. However, for pregnant women with pre-existing conditions like epilepsy and asthma, supplementation of conventional treatment with HMs may further complicate their care. The use of HMs is frequently not reported to healthcare professionals. Providers are often not questioning HM use, despite little being known about HM safety and HM-drug interactions during pregnancy. This lack of knowledge on potential toxicity and the ability to interact with conventional treatments may impact both mother and fetus. There is a need for education of women and their healthcare professionals to move away from the idea of HMs not being harmful. Healthcare professionals need to question women on whether they use any HMs or natural products during pregnancy, especially when conventional treatment is less efficient or/and some adverse events have occurred as herbal-drug interactions could be the reason for these observations. Additionally, more preclinical and clinical studies are needed to evaluated HM efficacy and toxicity.